The Program Minha Casa Minha Vida in Suzano - SP: socio-spatial aspects and segregation - Souza, Anderson Aparecido de; Santos, Leandro Bruno (Revista Cerrados, 2020)
The Program Minha Casa Minha Vida (PMCMV – My House My Life) is the current housing policy that was launched in 2009 by the Federal Government to solve the lack of access to housing for poor people. Besides offering subsidies and support to low-income families, this policy also aimed to promote economic growth by strengthening the civil construction sector. This paper aims to understand the socio-spatial implications of PMCMV in Suzano – SP, where approximately 1,800 people received access to housing. The methodological procedures used consisted of current literature searches and review, documentary investigations, secondary data collection, preparation and use of questionnaires, as well as systematization and analysis of data. The results show that, despite the PMCMV reproduces in Suzano a logic of socio-spatial segregation, with housing units in peripheral areas marked by environmental problems and the insufficient presence of urban equipment, it means a conquest for the beneficiaries, who stop living in areas of cliff, pay rent or depend on social rent.